A Material History of the Daśanāmī Maṭha of Bodhgaya. (14th June 2021) - Amar, Abhishek S
Abstract: This short essay examines the history of the Daśanāmī Giri maṭha of Bodhgaya, which has been largely ignored because of the focus on the Buddhist history of this site. Through a comparative study of nineteenth-century colonial accounts and documents, and material remains, this essay explores its claimed history and emergence as an important religio-political institution in the colonial period. In doing so, it specifically investigates network of samādhis across the villages of Gaya district and their role in establishing its position as an important zamindar.